Identifying current and future fish spawning habitat for fisheries management applications via oceanographic models: Case studies for Nassau Grouper (Epinephelus striatus) and Southern Flounder (Paralichthys lethostigma) - Bartlett, Brian S (East Carolina University)
For many fish species, spawning habitat is a smaller, but critical subset of overall habitat range. Spawning habitat contributes to both recruit abundance and metapopulation connectivity. As a result of these contributions, an understanding of spawning habitat dynamics is critical for managers to effectively manage a species. Further, due to climate change, many fish species' spawning habitats are likely to change, either in location or timing. The goal of this research was to utilize oceanographic models, coupled with biological models, to (1) assess the effectiveness of future spatiotemporal management on Nassau grouper under varying climate change, (2) investigate seasonal sea surface temperature changes as a biological cue for spawning under global warming, and (3) identify potential spawning grounds of southern flounder captured near Beaufort Inlet, NC. Results show that spawning habitat suitability declined by as much as 70% throughout the region by the end of the century compared to a historical baseline. Despite these declines, it was also shown that regions within marine protected areas had less severe declines than regions outside protected areas, suggesting that habitat refugia will be important for protecting Nassau grouper spawning habitat. It was also shown that the greater Caribbean Sea will experience uneven rates of temperature changes under global warming, with differences varying regionally and seasonally. Summer and winter experience the greatest changes, with species experiencing the highest impact from anthropogenic forces during the seasons they spawn. Finally, it was shown that the overall distribution of possible spawning sites of southern flounder varied from year to year, however the center of gravity was consistently in southern Onslow Bay, NC, across months and years. It was also shown that much spawning appeared to occur local to the capture site, but individual, long-distance dispersal events may help maintain genetic homogeneity throughout the stock. This research shows that utilizing climate models with biological modeling can provide important insight into fish spawning habitat currently, and under climate change. This work will be relevant to help protect species from overfishing and climate impacts via more knowledge-based management.
Keywords: species distribution modeling; particle dispersal modeling; Nassau grouper--Spawning--North Carolina--Outer Banks; Southern flounder--Spawning--North Carolina--Outer Banks; Nassau grouper--Habitat--North Carolina--Outer Banks; Southern flounder--Habitat--North Carolina--Outer Banks; Climatic changes; Climatology--Mathematical models; Fishery management--North Carolina--Outer Banks